Accuracy of Frozen Section Biopsy in the Diagnosis of Ovarian Malignancy : An Institutional Experience (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Women with early-stage ovarian cancer need surgical staging, which entails taking samples from areas within the abdominal cavity and retroperitoneal lymph nodes for further treatment. The frozen section is an essential and beneficial adjunct in the intraoperative diagnosis of ovarian tumors. The study aimed to evaluate the diagnostic accuracy of frozen section biopsy in malignant lesions among ovarian masses.Materials and methods: This was a cross sectional study. Thirty cases of ovarian masses from the patients who underwent laparotomy for ovarian massesat the Department of Obstetrics and Gynaecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, from March 2014 to August 2014 were included in the study. Surgical specimens were first processed for frozen section reporting, then processed routinely for final paraffin section histopathology evaluation. Results of frozen and paraffin sections were categorized as benignand malignant, and the accuracy of the frozen section was determined.Results: The mean age was found to be 35.6±12.4 years, with a range from 14 to 70 years. Frozen section biopsy for evaluation of ovarian masses, true positive was in 6 cases and no false, one false negative and true negative in 23 cases identified by histopathology. Frozen section biopsy has a sensitivity of 85.7%, specificity of 100.0%, accuracy of 96.7%, a positive predictive value of 100.0%, and a negative predictive value of 95.8% in the evaluation of malignant ovarian masses.Conclusion: The present study confirms that frozen section diagnosis is a reliable method for the surgical management of patients with ovarian masses.JCMCTA 2022 ; 33 (1) : 144-147